2022
DOI: 10.1101/2022.05.17.492189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERnet: a tool for the semantic segmentation and quantitative analysis of endoplasmic reticulum topology for video-rate super-resolution imaging

Abstract: The topology of endoplasmic reticulum (ER) network is highly regulated by various cellular and environmental stimuli and affects major functions such as protein quality control and the cell's response to metabolic changes. The ability to quantify the dynamical changes of the ER structures in response to cellular perturbations is crucial for the development of novel therapeutic approaches against ER associated diseases, such as hereditary spastic paraplegias and Niemann Pick Disease type C. However, the rapid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Many of the above results point towards a dysregulation of the ALP which is supported by previous studies showing aberrant FUS aggregation disrupts the latter (Baskoylu et al, 2022; Soo et al, 2015). We observe cytoplasmic to nuclear translocation of TFEB in the presence of FUS accumulation, which we relate to the higher intralysosomal pH measured in FUS cells.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Many of the above results point towards a dysregulation of the ALP which is supported by previous studies showing aberrant FUS aggregation disrupts the latter (Baskoylu et al, 2022; Soo et al, 2015). We observe cytoplasmic to nuclear translocation of TFEB in the presence of FUS accumulation, which we relate to the higher intralysosomal pH measured in FUS cells.…”
Section: Discussionsupporting
confidence: 75%
“…Despite using non-neuronal HEK293T and COS7 cells, we believe the underlying mechanisms observed should hold true for a more physiologically relevant model. In support of this, it was recently shown that there is impaired autophagy and neuronal dysfunction in a P525L-FUS knock in C. elegans model (Baskoylu et al, 2022). Moreover, our findings align with the fact that autophagy dysfunction occurs early on in disease pathology, which acts as an accelerator for neurodegeneration (Cortes and la Spada, 2019).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It enables accurate quantification of cell volume, shape, and intercellular spatial relationships, providing essential insights into biological processes. Particularly in areas like drug development, where the efficacy of treatments can be profoundly influenced by the 3D arrangement of cells and tissues, precise segmentation algorithms are indispensable 6,7 . Therefore, the development of advanced 3D cell segmentation algorithms is pivotal, given the intrinsic three-dimensional nature of biological tissue and cellular structures.…”
mentioning
confidence: 99%
“…In [27], the authors developed a deep residual-network model, ER-net, for the segmentation of ER. In follow-up work, ERnet-v2 [28], the authors used a Swin Transformer-based model to extract tubules, sheets, and sheet-based-tubules (SBTs) from the ER structure and provided quantitative measures to understand the topology of the ER network in a supervised manner. Garcia et al [29] developed a pipeline to quantitatively measure the areas of rough and smooth ER to assess the impact of different pharmacological perturbations on ER morphology.…”
mentioning
confidence: 99%